EVALUASI KELAYAKAN BISNIS PADA USAHASIOMAY AYAM SAMBAL GOANG (STUDI KASUS DI KOTA BANDUNG) - Deny Suteja Ginanjar R.G; Dewi Nurbaiti (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to evaluate the Business Feasibility the Sambal Goang Chicken Siomai from the legal, environmental, market and marketing, technical and technological aspects, human resource management, finance, and social aspects (Case Study in Bandung). The research method used was naturalistic qualitative. The Sambal Goang Chicken Siomai is one of the readymade processed food products andalso frozen food from Dapoer Ceu Giok's production. The results of the study stated that the Sambal Goang Chicken Siomai is declared feasible to be developed, this is assessed from legal aspect, environmental aspect, market and marketing aspect, technical and technological aspect, management and human resources aspect, financial aspect, and social aspect.